Nonalcoholic fatty liver disease in children with obesity– observations from one clinical centre in the Western Pomerania region - Marcinkiewicz, Katarzyna; Horodnicka-Józwa, Anita; Jackowski, Tomasz; Strączek, Kamila; Biczysko-Mokosa, Agnieszka; Walczak, Mieczysław; Petriczko, Elżbieta (Frontiers in Endocrinology, 2022)
Nonalcoholic fatty liver disease (NAFLD) is a growing health problem in the pediatric population, due to the constantly increasing percentage of children with excess body weight. The objective of the study was to assess the occurrence of NAFLD based on ultrasound (USG) analysis and the use of alanine aminotransferase (ALT) in children with excessive body weight depending on glucose tolerance. Medical records of 228 consecutive patients aged 2-18 years with excessive body weight were reviewed retrospectively. Based on the oral glucose tolerance test children were divided into groups according to the severity of carbohydrate metabolism disorders. ALT, lipid parameters and insulin sensitivity indices HOMA, Matsuda and Quicki were analysed. NAFLD was diagnosed (based on the USG) in 51 patients (23.61%) - the incidence in the impaired glucose tolerance (IGT) and type 2 diabetes (T2DM) group was significantly higher when compared to ones without glucose intolerance. Because of extreme values of metabolic parameters in TDM2 children being outliers, they were not considered in the statistical analysis of the study. 22 (11.58%) patients had elevated ALT values, of which 12 (54.55%) had hepatic steatosis features on ultrasound. 72.73% (n=32) patients with fatty liver features on USG had ALT values considered normal with cut-off point 42 U/l accepted in this study. Almost every fourth obese child in the study group presents features of fatty liver in ultrasound examination. Although ultrasound is not rec-ommended by North American Society For Pediatric Gastroenterology, Hepatology &Nutrition(NASPGHAN) for the diagnosis of NAFLD in children, it allows identifying a high percentage of children with features of fatty liver. This percentage increases significantly in children with glucose intolerance.